Biomecânica do membro inferior durante o single-leg drop vertical jump: implicações para a reabilitação na tendinopatia patelar e na reconstrução do ligamento cruzado anterior - Martinez, Adalberto Felipe (Universidade Federal de São Carlos, 2022)
Many sports activities contain jumping and landing component exposing athletes to high joint loads. Consequently, these athletes have a high incidence of acute and overuse injuries such as anterior cruciate ligament (ACL) rupture and patellar tendinopathy (PT), respectively. In jumping athletes, the incidence of PT ranges from 11.8% to 50% according with sport level and what kind of sport. Regarding ACL injuries, up to 121 injuries per 100,000 people/year. Athletes who undergo ACL reconstruction are subject to second ACL injury or knee osteoarthritis. Considering the possible influence of biomechanical factors in these injuries, the objectives of this thesis was to verify factors associated with knee joint overload during landing phase of single leg drop vertical jump and its implications for rehabilitation of PT and for athletes with ACL reconstruction. In this thesis, two studies were carried out. In the first study, the objective was to evaluate the association between peak ankle dorsiflexion and ankle dorsiflexion excursion during landing with peak vertical ground reaction force (vGRF), vGRF load rate, peak patellar tendon force, patellar tendon force load rate and peak ankle plantar flexor moment during landing phase of single-leg drop vertical jump task. In this way, a three-dimensional biomechanical analysis of 26 healthy recreational jumping athletes was performed using a camera system synchronized to a force plate. Ankle dorsiflexion excursion was negatively correlated with vGRF loading rate and positively with ankle plantar flexor moment. In addition, there was a positive correlation between ankle dorsiflexion peak and vGRF peak. In the second study, the objective was to compare the peak of the vGRF, peak moments, hip, knee and ankle moments in the peak of the vGRF and total support moment during landing phase of single-leg drop vertical jump between the involved and uninvolved limb of athletes with ACL reconstruction and heathy control athletes. For this purpose, using the same methodology of first study, 12 athletes with ACL reconstruction with hamstring ipsilateral grafts (GRLCA) and 14 healthy recreational control athletes (GC) were assessed. Peak of vGRF and knee extensor moment at peak of vGRF were higher in the involved limb of reconstructed athletes than in the control athletes. From these two studies, we concluded that: 1- lower ankle dorsiflexion excursion is associated with a greater vGRF loading rate, but there is no association between ankle kinematics and patellar tendon loads; and 2- Compared to the control group, the involved limb of the ACLRG presents greater vGRF and greater knee extensor moment at peak of vGRF during SLDVJ landing. These results suggest that greatest load occurs on the ACL graft at the time of the peak of vGRF.
Biomechanics lower limb biomechanics during the single-leg drop vertical jump: implications for patellar tendinopathy and anterior cruciate ligament reconstruction rehabilitation
Keywords: Joelho de saltador; Biomecânica da aterrissagem; Sobrecarga no joelho; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL